Pemberdayaan Masyarakat dalam Pencegahan Hiperkolesterolemia melalui Edukasi dan Pemberian Teh Daun Alpukat - Eka Deviany Widyawaty; Chusnul Zulaika (Health Care : Journal of Community Service, 2025)
Hypercholesterolemia is one of the main risk factors for cardiovascular disease, which can be prevented through community-based interventions. This activity aims to increase public knowledge about hypercholesterolemia and introduce avocado leaf tea as a herbal alternative. The methods used include direct education, total cholesterol level examination before the intervention, and the distribution of avocado leaf tea to the community in Nusukan Subdistrict, Surakarta. Active compounds such as flavonoids, saponins, and tannins found in avocado leaves are believed to have cholesterol-lowering effects. The results of the activity showed an increase in knowledge and good acceptance of avocado leaf tea consumption. This approach demonstrates the effectiveness of the herbal-education strategy in efforts to prevent hypercholesterolemia at the community level.